Medicinal plant uses and names from the herbarium of Francesc Bolòs (1773–1844). (23rd May 2017) - Gras, Airy; Garnatje, Teresa; Ibáñez, Neus; López-Pujol, Jordi; Nualart, Neus; Vallès, Joan
Abstract: Ethnopharmacological relevance: Ethnobotany takes into account past uses to be projected into the present and future. Most current ethnobotanical research is focused, especially in industrialised countries, on obtaining information of plant uses from elderly people. Historical ethnobotany is less cultivated, although papers have demonstrated its interest. Particularly poor, but potentially very relevant, is the attention paid to historical herbaria as a source of data on useful plants. Aims of the study: Bearing this in mind, we studied the herbarium of the Catalan pharmacist and naturalist Francesc Bolòs (1773–1844), which contains information on medicinal uses and folk names, with the aim of establishing a catalogue of plants and uses and tracing them through old and contemporary literature. Methodology: The ca. 6000 plant specimens of this herbarium were investigated to assess those including plant uses and names. These taxa have been thoroughly revised. The data have been tabulated, their biogeographic profile, possible endemic or threatened status, or invasive behaviour have been assessed, and the content regarding medicinal uses, as well as folk names, has been studied. The medicinal terms used have been interpreted as per current days' medicine. The popular names and uses have been compared with those appearing in a certain number of works published from 11th to 20th centuries in the territories covered by the herbarium and with all the data collected in 20th and 21st centuries in an extensive database on Catalan ethnobotany. Results: A total of 385 plant specimens (381 taxa) have been detected bearing medicinal use and folk names information. We collected data on 1107 reports of plant medicinal properties (in Latin), 32 indications of toxicity, nine reports of food use, and 123, 302 and 318 popular plant names in Catalan, Spanish and French, respectively. The most quoted systems are digestive, skin and subcutaneous tissue (plus traumatic troubles) and genitourinary. Relatively high degrees of coincidence of plant names and uses in the herbarium and the literature comparison set have been found. Of the taxa contained in this medicinal herbarium, 294 were native to the Iberian Peninsula, and 86 were alien. Neither endemic nor threatened taxa have been detected, whereas a considerable portion of the alien taxa shows invasive behaviour at present. Conclusions: Our analyses indicate a certain degree of consistency between the medicinal uses of plants recorded in this 18th and 19th century herbarium and the records found in the literature and in recent ethnobotanical datasets, accounting for the robustness of pharmaceutical ethnobotanical knowledge in the area considered. Data appearing on the specimen labels are numerous, pointing out the herbarium as a relevant source of ethnopharmacological information. Special attention should be paid to some original uses contained in the herbarium's labels for further investigation on plant properties and drug design. Graphical abstract: